ANALISIS STRATEGI DIPLOMASI ANGKATAN LAUT DALAM RANGKA MENINGKATKAN HUBUNGAN BILATERAL PERTAHANAN INDONESIA DAN KOREA SELATAN - Khoirul Hadi Prayitno; Jales Jamca Jayamahe; Endah Palupi (UJoST- Universal Journal of Science and Technology, 2023)
The defense bilateral relationship between Indonesia and South Korea has an important role in maintaining stability and security in the Southeast Asian region. In an effort to strengthen this relationship, the naval diplomacy strategy of the two countries plays a significant role. This study aims to analyze the strategy of naval diplomacy in order to improve bilateral defense relations between Indonesia and South Korea. Naval diplomacy is an important aspect in strengthening defense cooperation between countries, especially in the context of the Indonesia-South Korea bilateral relationship. This study uses the NVivo software to collect, organize, and analyze qualitative data related to the naval diplomacy strategy of the two countries. The research method used involves analysis of document content, interviews with Navy officials, and surveys of expert opinions in the field of military diplomacy. The results of this study reveal various naval diplomacy strategies that have been implemented to strengthen bilateral defense relations between Indonesia and South Korea. Some of the identified strategies include joint military training cooperation, naval exchange visits, and public diplomacy efforts to increase public understanding of the importance of this collaboration. This research also describes the important role of NVivo software in helping researchers organize and analyze complex qualitative data. By using NVivo, researchers can identify key patterns in the naval diplomacy strategy and gain deeper insights on how bilateral defense cooperation can be strengthened. The findings of this study have important implications for the development of bilateral defense relations between Indonesia and South Korea, as well as provides a broader view of the importance of military diplomacy in the context of international relationss